Relations between buckling & vibrational characteristics of coupled shear walls. (June 2021) - Tong, Genshu; Lin, Chenhao
Abstract: This paper developed relations between buckling and vibrational characteristics of coupled walls systems. The buckling behavior and the vibrational period of coupled shear walls with multiple wall piers as well as with varied cross-sectional rigidities and axial forces along the height are studied. A simple model, considering coupled shear walls as implicit dual structural systems consisting of a flexural-type substructure B1 and a flexural-shear-type substructure BS2, was proposed to help understand the structural behavior of coupled shear walls. Based on the continuous method, the buckling equilibrium differential equations of coupled shear walls were derived and solved. Simple equations for the determination of structural lateral stiffness, critical loads, and natural frequencies are presented and verified against the linear elastic analysis results or numerical models developed by ANSYS. Finally, the relations between buckling load factors and vibrational periods of coupled shear walls are developed, the upper limit of periods are then derived to be used as a convenient tool for limiting the second-order effect in a residential building.